Teaching Aids In Learning Communication: The Introduction Of The Animals Concept To Students With Visual Impairment In Biology Lesson - Nurzaman, Mohammad; Hafiar, Hanny; Dewi, Retasari; Budiana, Heru Ryanto; Silvana, Hana (Journal of physics. Conference series, 2020)
Teaching aids are needed in an effort to explain biology material in order to be able to provide an overview, so students can develop concepts to form a comprehensive understanding. Concepts in biology learning materials are difficult to obtain by students with visual impairments without the support of teaching aids. The purpose of this study was to identify ways to introduce animals as living things to students with visual impairments. The method used in this research is a descriptive case study, with qualitative data types. The introduction of the concept of diversity of animals as living things, to students with visually impairment requires the complete teaching aids which include miniatures, for the introduction of shapes and structures; prototype textures, for the introduction of textures, feathers, scales, muscle tissue; audio, to recognize the distinctive sound of animals; An explanation of the description of the size, nature, character, usefulness in life, and behavior that needs to be developed. Constraints encountered in learning biology by using teaching aids for students with visual impairment, including among others: The unavailability of certain teaching aids that are sold and can be bought in the market; The teaching aids available have not been able to help students get an overall picture; The teaching aids available are not in accordance with the special conditions of students with visual impairments; The complexity of the system in some biology subject matter requires visual experience to understand it; In discussing a particular subject matter, the student with visual impairment requires several teaching aids that are operated simultaneously.